Become Captain of Your Financial Ship, Unit 1: Charting the Course - Josephine Turner (EDIS)
FCS7221, a 27-page curriculum by Josephine Turner, is Unit 1 in a series on personal financial management. It includes a slide presentation and a fact sheet and set of worksheets on money management that will help consumers understand their goals, their net worth, and their spending habits, and then develop a spending plan. Published by the UF Department of Family, Youth and Community Sciences, January 2007.